Correlation analysis between inflammatory biomarkers and significant clinical phenotypes of chronic obstructive pulmonary disease - Ekaterina A. Orlova; Bogdan Yu. Kuzmichev; Mihail A. Orlov; Inna P. Dorfman (Research Results in Pharmacology, 2023)
Introduction: Chronic obstructive pulmonary disease (COPD) is the leading cause of mortality. Using the evidence obtained about various clinical phenotypes of patients with the same disease allowed us to expand our understanding of the treatment of COPD. Nowadays the only option for solving the problem will be the definition of the clinical phenotype of COPD, and the receipt of expanded data on its correlation with respiratory and other significant biomarkers. Materials and methods: We analyzed the correlations between FKN, CRP and TBA-active lipid peroxidation products in 373 patients with various COPD phenotypes and 60 healthy volunteers. Enzyme immunoassay was used to study the levels of inflammatory biomarkers. Results: We have identified a statistically significant increase in the levels of inflammatory biomarkers in patients with COPD compared with the control. The FKN level in the group of patients with COPD was 1.3 ng/ml, which was higher (p<0.001) than in the control (FKN level of 0.3 ng/ml, p<0.001). The CRP level in patients with COPD was 27.8 mg/L, whereas in control the CRP level was 1.2 mg/L (p<0.001). The TBA-active lipid peroxidation products level in patients with COPD was 14.5 mmol/L, which was higher when compared to the control (p<0.001). Discussion: The correlation analysis revealed very strong relationships between the levels of all the biomarkers studied. The highest values of the Kendall rank correlation coefficient (τ) were determined between the levels of all the inflammatory biomarkers in subgroups of patients with chronic bronchitis and mixed COPD phenotypes. Conclusion: Detection of the COPD phenotype will help actively monitor the therapy of COPD exacerbations.